SCIENCE CITY: INNOVATION AND EDUCATION (BY THE EXAMPLE OF DUBNA TOWN) - Khozyainov, Mikhail; Yakushina, Olga (Revista Inclusiones, 2020)
In the article, the study of innovative development directions in Russia was undertaken. Statistical data, regulations have been used and analyses of published literature sources have been carried out. The possibility of creating a national innovation system through the formation of regional innovation-oriented development centers, techno-parks, technopolises, territorial clusters, science cities was investigated. A comparison of the territorial production complexes and regional innovationoriented centers of development was has been carried out. The selection effectiveness of science centers as the points of innovation growth has been shown. Science cities are also the structureforming settlements at the state level like megapolises, ancient cities, cultural and religious centers, wildlife sanctuaries and many other things.